Problems of legal regulation of parents' maintenance obligations in the Republic of Kazakhstan - Ilyassova, G.A. (Вестник Карагандинского университета, 2016)
The article studies the legal norms of national and international family law governing of parents' maintenance obligations to maintain minor children. Analyzed statistical data, practical cases on recovery of alimony debt in Kazakhstan. The aim of the study is to improve the protection mechanism of the interests of minor children in need of financial support. The author formulated the conclusions and suggestions on improving the exist- ing family legislation of the Republic of Kazakhstan taking into account experience of foreign countries.
Keywords: maintenance obligations; minors, parents; child support collection